2004
DOI: 10.1007/s00228-004-0838-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure and markers of appropriateness, quality and performance of drug treatment over a 1-year period after hospital discharge in a cohort of elderly patients with cardiovascular diseases from Germany

Abstract: In a group of elderly patients over 65 years of age with at least two cardiovascular diagnoses requiring chronic medication (n=424), drug therapy at hospital discharge and at home thereafter was followed for a 1-year period. Two home visits took place at 3 months and 12 months after initial discharge. A median of six prescriptions had already been given at the time of discharge; this number increased slightly during ambulatory follow-up. After 1 year, about 30% of the patients had to take more than ten dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
7
0
5
Order By: Relevance
“…There has been a global increase in statin utilization with the emergence of RCT evidence in the past 5 years (55-57) and a few regional increases with the use of knowledge translation programs and quality control initiatives (58 -60). However, recently reported utilization rates of 40% to 60% in elderly patients with active CHD remain suboptimal (5)(6)(7)(8). It is crucial to disseminate the evidence for statins in elderly patients with CHD to increase current utilization rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been a global increase in statin utilization with the emergence of RCT evidence in the past 5 years (55-57) and a few regional increases with the use of knowledge translation programs and quality control initiatives (58 -60). However, recently reported utilization rates of 40% to 60% in elderly patients with active CHD remain suboptimal (5)(6)(7)(8). It is crucial to disseminate the evidence for statins in elderly patients with CHD to increase current utilization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary heart disease (CHD) is the leading cause of death among elderly patients, with Ͼ80% of coronary deaths occurring in patients over the age of 65 (1). Despite the See page 46 recommendation of the third National Cholesterol Education Program Adult Treatment Panel to intensively lower lipids in elderly patients with CHD (2)(3)(4), statin utilization continues to be 40% to 60% in elderly patients after myocardial infarction (MI) (5)(6)(7)(8). Utilization is suboptimal because evidence has not consistently shown that statins reduce mortality in elderly patients (9 -13).…”
Section: Discussionmentioning
confidence: 99%
“…Himmel et al (2004) found changes of about 30% in antihypertensive and cardiac drugs after hospital admission independent of whether the patient was admitted because of cardiac disease or other medical problem. In a 1-year follow-up study, about 50% of all cardiovascular prescriptions were subject to changes in the choice of preparation (brand-generic) or within classes of similar agents prescribed (Harder et al 2005). In a study by Katz et al (1996), treatment changes were almost as common in patients admitted with stable cardiovascular disease as in those requiring rapid drug intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This may indicate that some of the attending physicians focused on symptomatic treatment of the medical condition. Patients with ACS took an average of six medications and patients with stroke took an average of five medications, which is in the upper range reported in the literature (Hach et al 2005;Harder et al 2005). It was also found that polypharmacy can be caused by treatment according to evidence-based therapeutic guidelines, which is particularly problematic for elderly and multi-morbid patients (Meinertz and Kähler 2005).…”
Section: Discussionmentioning
confidence: 94%